Racism in Europe: Characteristics and Intersections With Other Social Categories - Ball, Elena; Steffens, Melanie C.; Niedlich, Claudia (Frontiers in Psychology, 2022)
Concerning race and its intertwinements with gender, sexual orientation, class, accents, or ability there is a scarcity of social psychological research in Europe. Applying an intersectional approach to the study of racism in Europe allows detecting specific experiences of discrimination. The prevalent understanding of European racism is connected to migration from the former colonies to the European metropoles and the post-Second-World-War immigration of ‘guest workers’. Thus, the focus of this research is on work-related discrimination. Against the backdrop of a short historical review, we present the results of the few existing studies in Europe on intersectional discrimination within the labor market and discuss what can be learned from them. The pattern of findings is more complex than the assumption that individuals belonging to two or more marginalized social categories are always the most discriminated ones. Rather, gender, sexual orientation, and origin interact with the specific job context in determining whether minority individuals are discriminated against or even preferred over individuals belonging to the majority group. We argue that considering the stereotype content model and social-identity theory helps to structure the sometimes contradictory results. The review presents thus new perspectives on racism in Europe based on current research, develops hypotheses on the interplay of intersecting identities, and identifies four novel research questions based on racist attributions considering situational variables: These are the role of concrete job contexts in explaining (no) discrimination, the influence of different stereotypes regarding marginalized groups, and the explanatory value of sexual orientation and class or socioeconomic-status in terms of some patterns of results.